Informal settlements: Da concepç\~ao do termo à sua transformaç\~ao em agenda quente de pesquisa - Análise cientométrica e difus\~ao acadêmica - Renato Nunes Balbim; Cristine Diniz Santiago (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– This is the third in a series of four Discussion Papers (DP) that make up the research How Cities are Divided: the invention of informal settlements. The goal of this series was to carry out a culturomic and scientometric study on the use of the term informal settlements contextualized by previous geopolitical and public policies analysis. Specifically here, the scientometric study is presented, which points to a mostly functional and interdisciplinary use of the term, with emphasis on African as a diffuser of publications and the Global North as their main funding source. Nevertheless, there are indications of critical use of the term, on a smaller scale, as well as evidence of the relevance of international agencies in its diffusion. The last publication in the series will bring together the findings and contextualized discussions.
10419/284891
Keywords: R28; H76; O18; 330; informal settlements; urban management; bibliometric analysis; UN-Habitat; slum